The Influence of the Internet on Politics (Comparative Case Study in China, Japan, Korea, and Indonesia) - Irwanysah - (The Indonesian Journal of Communication Studies, 2008)
The Internet is a necessity for people around the world including Asia. It is a means to connect politicians, political party supporters, activists, and the parties themselves. The advent of Internet cafes and email has greatly enabled the integration of global communication. At the same time, the emerging cyber culture of the Internet challenges the very notions of sovereignty, government, political parties, civil society, and conventional politics in China, Indonesia, Japan, Korea, and throughout the Asia-Pacific region. The political context of Internet usage differs throughout the Asia-Pacific region, but certain concerns are common to the role the Internet plays in the region. Will the Internet create a political culture that undermines conventional politics? And will Internet usage in Asia result in the creating of local cultural content, strengthen regional diversity and enhance political maturity? To answer the questions, the paper will present some cases of the Internet’s impact to politics in China, Indonesia, Japan, and South Korea. Then, the paper will describe some of the similarities between the cases. Finally it will conclude with some conceptual ideas as to what Indonesia can learn about Internet-based politics from these cases.